Standardizing the world income inequality database - Frederick Solt (Luxembourg Income Study (LIS), 2008)
Cross-national research on the causes and consequences of income inequality has been hindered by the limitations of existing inequality datasets: greater coverage across countries and over time is available from these sources only at the cost of significantly reduced comparability across observations. This article presents the Standardized World Income Inequality Database (SWIID), which standardizes the United Nations University database (UNU-WIDER 2008) while minimizing reliance on problematic assumptions by using as much information as possible from proximate years within the same country. The resulting series of gross and net income inequality data maximize comparability for the largest possible sample of countries and years and so are better suited to broadly cross-national research than other sources.
Keywords: 330; Einkommensverteilung; Statistische Daten; Welt